The selected papers of Margaret Sanger. - Sanger, Margaret, 1879-1966 (University of Illinois Press, 2016)
When Margaret Sanger returned to Europe in 1920, World War I had altered the social landscape as dramatically as it had the map of Europe. Population concerns, sexuality, venereal disease, and contraceptive use had entered public discussion, and Sanger's birth control message found receptive audiences around the world. This volume focuses on Sanger from her groundbreaking overseas advocacy during the interwar years through her postwar role in creating the International Planned Parenthood Federation. The documents reconstruct Sanger's dramatic birth control advocacy tours through early 1920s Germany, Japan, and China in the midst of significant government and religious opposition to her ideas. They also trace her tireless efforts to build a global movement through international conferences and tours. Letters, journal entries, writings, and other records reveal Sanger's contentious dealings with other activists, her correspondence with the likes of Albert Einstein and Eleanor Roosevelt, and Sanger's own dramatic evolution from gritty grassroots activist to postwar power broker and diplomat.